2021
DOI: 10.1063/5.0044898
|View full text |Cite
|
Sign up to set email alerts
|

Homogeneous water nucleation in carbon dioxide–nitrogen mixtures: Experimental study on pressure and carrier gas effects

Abstract: New homogeneous nucleation experiments are presented at 240 K for water in carrier gas mixtures of nitrogen with carbon dioxide molar fractions of 5%, 15%, and 25%. The pulse expansion wave tube is used to test three different pressure conditions, namely, 0.1, 1, and 2 MPa. In addition, a restricted series of nucleation experiments is presented for 25% carbon dioxide mixtures at temperatures of 234 and 236 K at 0.1 MPa. As pressure and carbon dioxide content are increased, the nucleation rate increases accordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 67 publications
0
14
0
Order By: Relevance
“…In , Luijten and van Dongen showed that nucleation phenomena of condensable vapors in a carrier gas can be considered as unary nucleation if x g,eq << (S − 1)∕S , with x g,eq the dissolved gas fraction in the bulk liquid. With a maximum carrier gas solubility x CO 2 ,eq < 0.038 in our experiments (see supplementary material of Campagna et al 2021), this condition was always fulfilled. For carrier gases with a much larger x g,eq , the full binary nucleation model applies (Looijmans et al 1995).…”
Section: Experimental Methodology Overviewmentioning
confidence: 54%
See 4 more Smart Citations
“…In , Luijten and van Dongen showed that nucleation phenomena of condensable vapors in a carrier gas can be considered as unary nucleation if x g,eq << (S − 1)∕S , with x g,eq the dissolved gas fraction in the bulk liquid. With a maximum carrier gas solubility x CO 2 ,eq < 0.038 in our experiments (see supplementary material of Campagna et al 2021), this condition was always fulfilled. For carrier gases with a much larger x g,eq , the full binary nucleation model applies (Looijmans et al 1995).…”
Section: Experimental Methodology Overviewmentioning
confidence: 54%
“…The experimental data (Campagna et al 2020a(Campagna et al , 2021 used for the analysis of the present work were carried out with the Pulse Expansion Wave Tube (PEWT). A schematic of the facility is reported in Fig.…”
Section: Experimental Methodology Overviewmentioning
confidence: 99%
See 3 more Smart Citations